Que futebol é esse? Uma análise das representações do futebol feminino no site globoesporte.com - Corrêa, Lucas Brum (2018)
The present work aims to analyze the way in which representations of women 's football take place on globoesporte.com. We worked mainly with authors of Cultural Studies, a social, political and intellectual movement concerned that cultural processes happen in a fair and egalitarian way in society, from a conception of complex and active culture. We have specific objectives that guide this research: to problematize reflections about the gender cut in Brazilian soccer; to verify how the themes related to women's football are positioned on the news site searched; To understand how the mediation of representations of women's football and the processes of inclusion and exclusion take place. To fulfill these tasks we use the methodology of cultural analysis, also associated to a qualitative online observation, from the development of a proper course of analysis. The analysis of culture takes place through three different dimensions: social, documentary and institutional, and is concluded in the sphere of mediation, an instance that articulates the three dimensions that help to compose a portrait of the media representations of women's football. It was possible to perceive that the processes of construction of the representations are connected to a wider social context and are mediated by several elements. Representations with traces of silence, inclusion, gender bias and indifference were identified.